Zarządzanie nowoczesnym szpitalem - analiza technicznej efektywności - Strzelecka, Agnieszka; Nieszporska, Sylwia (The Modern Hospital Management - Technical Efficiency Analysis, 2006)
The hospitals are recognized as the most important institutions of medical service in consideration of character at giving services and incurring costs. These institutions (their weight and meaning) determine the proper opinion of economic situation at health system and permit for qualify the directions in management the health care. Estimation of the economic efficiency at hospitals is examined how in production process, the inputs at medical services influence on achieved results (outputs). Taking the above into account the general hospitals in Poland with regard to the division of regional country in year 2002 are analysed in present paper. Their technical
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 213-224